PENERAPAN METODE SPRINGATE DALAM MENILAI KEBANGKRUTAN PADA SUBSEKTOR PERKEBUNAN DI LAHAN BASAH - Ali Sadikin -; Fahmi Roy Dalimunthe (Universitas Lambung Mangkurat, 2022)
The purpose of this research to analyze and determine the application of the springate method in bankruptcy in the plantation sub-sector in wetlands listed on the Indonesian stock exchange for the 2017-2019 period. The total population of the study was 19 companies in the plantation sub-sector, while the number of samples was 14 companies using the porpusive sampling method. The results of this study indicate that in 2017 there were 6 plantation sub-sector companies that were predicted to experience Non-Financial Distress conditions and 8 companies were predicted to experience Financial Distress conditions. In 2018 there are 4 companies that are predicted to experience Non-Financial Distress conditions and 10 companies are predicted to experience Financial Distress conditions. In 2019, there were 2 plantation sub-sector companies that were predicted to experience Non-Financial Distress conditions and 12 that were predicted to experience Financial Distress conditions. Keywords: Springate method, Financial distress